TOXICOLOGICAL AND SOME REPRODUCTIVE ASPECTS OF THE EFFECTS OF ALCOHOLIC EXTRACT OF COCONUT ON MALE ALBINO MICE - Maissam Hassan Ali; Ala Al-Deen Hassan Jawad (Basrah Journal of Veterinary Research)
In this study, two experiments had been done: Experiment (1), was designed to determine the acute toxicity of alcoholic extract of coconut ( Cocos nucifera ) fruit to the laboratory mice. Eight groups (6 mice each) of male albino mice were used in this experiment. The first group was drenched (1ml) physiological saline (as control group), while the other seven groups were given orally ascending doses (0.25, 0.5, 1, 1.5, 2, 2.5, 3 g/kg B.W.) respectively. After (24hr), all groups of mice were inspected for the presence of dead mice. The results of this experiment showed no mortality in all groups of mice and the extract is not toxic. Experiment (2), this study was designed to investigate the effect of alcoholic extract of coconut fruit on the efficacy of reproductive system of male mice. For this purpose, (24) mature male mice were allocated equally and randomly into three groups. Group (1) was given physiological saline and was considered as control group. Group (2) and group (3) were given 125mg/kgB.W./day and 200 mg/kg B.W. /day of alcoholic extract of coconut fruit respectively. All mice in the three groups received orally the appropriate treatment for 15 days. Post treatment, two criteria were chosen as indicators for the efficacy of the extract. The first one was relative testicular weight to body weight. The other one was the concentration of sperm in caudal part of epidydemis. The results of this experiment revealed that there was a significant (P